PERAN KEPEMIMPINAN STRATEGIS DALAM PENYELENGGARAAN PELATIHAN MILITER GUNA MENINGKATKAN KINERJA ANGKATAN BERSENJATA - Alrumeh, Abdullah; Haryanto, Agus; Agus Hariadi, Prasetiyo (Penerbit Lafadz Jaya, 2025)
The evolving dynamics of global security demand continuous adaptation and capability enhancement by the armed forces, making strategic leadership and military training essential. This study analyzes how strategic leadership influences training implementation and improves military performance, identifies existing challenges, and formulates optimization strategies. Using a qualitative approach with insights from key informants, the findings reveal that strategic leadership plays a pivotal role through experience, adaptability, communication, and organizational culture. However, challenges persist, including inadequate leader qualifications, substandard facilities, administrative complexity, and limited managerial human resources. The study concludes that strengthening strategic leadership is vital for enhancing training effectiveness. Optimization efforts should focus on comprehensive data provision, enforcing high-quality standards, selecting competent leaders, and improving leadership roles in training governance planning to significantly boost armed forces performance.